2017
DOI: 10.1080/21548331.2017.1400368
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of health promotion status in specialized hospitals associated with Hamadan University of Medical Sciences: health-promoting hospitals

Abstract: The findings indicated that HPH standards are very low in the studied hospitals. The reason behind this wide gap might be due to the fact that hospitals in Iran are more treatment-oriented and patient-oriented and they do not play an active part in health promoting. It was found that management policy and promoting healthy workplace standards had the worst status and must be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Hospitals in other developing and developed countries had a better score in HPH standards (7,13). These differences may be due to this fact that in Iran hospitals are more treatmentoriented and had little role in educating and promotion of healthy life style (14).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hospitals in other developing and developed countries had a better score in HPH standards (7,13). These differences may be due to this fact that in Iran hospitals are more treatmentoriented and had little role in educating and promotion of healthy life style (14).…”
Section: Discussionmentioning
confidence: 97%
“…East Azerbaijan hospitals had the lowest score (47.79±19.12) in standard 4 (Promoting a healthy workplace). In a study in Hamadan, Hamidi et al also reported the lowest score for standard 4 among the all HPH standards (14). This showed that although hospitals had a proper function in promoting health-related problems of patients, its role in promoting a healthy place for their staff was not appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the hospital has difficulties in managing health promotion as they were more focused on medical treatment. 7 HPH program create many health benefits, which includes patient expectation, perceived value, satisfaction, and loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…The patient experienced that the health care staff provided two essential components in HPH, that is, patient assessment and intervention. 7 Health promotion in the hospital need to be vigorously developed through interdisciplinary teamwork, shared decision-making processes involving patients and families, and deliver evidence-based health promotion. Previous studies analyzed the steps needed to improve patient loyalty through the HPH, however, limited studies were carried out on its use in the public sector.…”
Section: Introductionmentioning
confidence: 99%